An experimental study of the effect of uncertainty representation on decision making - Durbach, Ian N.; Stewart, Theodor J. (European journal of operational research, 2011)
► How uncertainty is represented exerts a significant influence on decision making and the alternative that is eventually chosen. ► For the tasks performed in this study, the use of probability distributions appeared to overload subjects, leading to relatively poor choices. ► Subjects seemed to derive benefit from formats providing some intermediate level of summary of the full probability distributions, specifically quantiles and scenarios. ► Uncertainty format has a significant effect on the level of difficulty experienced, with the level of difficulty experienced increasing with the quantity of information provided. ► The use of standard deviations becomes more difficult relative to other uncertainty formats as the number of objectives increases. This paper presents the results of an experiment investigating the effects of using different formats for representing uncertain attribute evaluations on decision making. Study participants make a series of hypothetical choices using six uncertainty formats – probability distributions, expected values, standard deviations, three-point (minimum–median–maximum) approximations, quantiles, and scenarios – and effects on decision making are tracked in terms of the quality of the final choice, the specific characteristics of the selected alternatives, and the difficulty experienced in making a decision. The results provide insights into how subjects make single- and multi-criteria choices in the presence of uncertainty (and some format for representing uncertainty) but in the absence of any real facilitation. The use of probability distributions appeared to overload subjects with information, leading to poorer and more difficult choices than if some intermediate level of summary was used – in particular three-point approximations or quantiles.